Patrimonio cultural en Quito: ¿qué lo amenaza y cómo se lo preserva? - Núñez Zabala, Milagros Soledad (2020)
On September 8, 1978, the United Nations Organization for Education, Science and Culture, known as UNESCO, named the city of Quito as the First Cultural Heritage of Humanity. This is because it is considered that the Historic Center is the largest and best preserved in Latin America and also has all the characteristics that appear in the articles for a city to be named cultural heritage. Based on this, the authorities on duty have carried out projects and allocated a budget for its preservation and conservation, since it is a commitment that the city must fulfill by keeping the heritage in good condition. Unfortunately natural and human threats deteriorate and destroy the heritage and national identity that goes hand in hand with this. Among the entities in charge that are concerned with the conservation and preservation of the Cultural Heritage of Humanity, the Cultural Heritage Salvage Fund (FONSAL) was created in 1987, which is currently the Metropolitan Institute of Heritage (IMP), UNESCO, the Ministry of Culture, the Undersecretariat of Culture that belongs to the municipality and the Municipality of Quito. These institutions are aware of the projects and planning that are underway for the restoration of heritage. A factor against that exists for the entities is the reduction of the global budget that they received annually, because by government decisions it has been proposed to distribute amounts designated annually by departments and institutions for the creation of these plans. Interviews and testimonies were also included with perspectives and knowledge of specialists in the field of art, architecture, municipal, heritage and history, where new edges were discovered that complement the information previously investigated.